Kajian Pemanfaatan Tanaman Tradisional Indonesia untuk Perawatan Kulit atau Rambut - Muhammad Hafid Dinata; Cinta Alivia Atha; Erinda Putri Dewiyanti; Woro Anindito Sri Tunjung; Khairul Anam; Fajar Sofyantoro (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Ethnobotany is a scientific approach used to explore the potential of plant species traditionally utilized by communities. This study aims to analyze the utilization of plant types and parts, as well as their phytochemical contents, for skin and hair care among the Indonesian population. The data from this research enriches the understanding of the rich ethnobotanical knowledge and practices related to skin and hair care among the Indonesian populace. The methodology employed involves a combination of survey methods and comprehensive literature analysis. Survey data was collected from 62 respondents from 22 different geographic regions in Indonesia. The survey results revealed the usage of 15 plant species from 13 families by the Indonesian community for skin or hair health maintenance. Based on literature review, it was found that most of these plants contain compounds such as flavonoids, alkaloids, saponins, and tannins. According to the literature study, these compounds have been proven to provide significant benefits in skin or hair care.